2009
DOI: 10.1038/jp.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in neonates and young infants: a report of 25 patients with platelet counts of ⩾1 000 000 μl−1

Abstract: Objective: Thrombocytosis has been reported in neonates and young infants, but little is known of its prevalence, timing of onset, associated conditions, sequelae and outcomes. To better understand this condition, we used the data repositories of a multi-hospital health-care system to identify all individuals p140 days old (20 weeks) who, during the past 6 years, had a platelet count of X1 000 000 ml À1 . Study Design:We identified all infants with extreme thrombocytosis (using the Sutor definition of a platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Most case reports and series report very low risk of complications when thrombocytosis is reactive and if no other risk factors are present . However, extreme thrombocytosis still causes great concern in pediatric care and raises the question of the need for prophylaxis/treatment.…”
mentioning
confidence: 99%
“…Most case reports and series report very low risk of complications when thrombocytosis is reactive and if no other risk factors are present . However, extreme thrombocytosis still causes great concern in pediatric care and raises the question of the need for prophylaxis/treatment.…”
mentioning
confidence: 99%
“…However, few authors reported normalization of platelet count after approximately one month of iron therapy. 21,26…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients with thrombocytosis are at risk for thromboembolic and hemorrhagic complications, 5 and have poorer outcomes after an acute vascular event. Neonatal thrombocytosis appears to be rarely associated with complications, although few studies have analyzed clinical characteristics of affected patients.…”
Section: Introductionmentioning
confidence: 99%